De hand aan de ploeg... : sociale uitsluiting in plattelandsgebieden - Knops, Guido; Alleman, Johan; Vasseur, Ann (Brussel: Koning Boudewijnstichting, 2001)
"Guido Knops; Johan Alleman; Ann Vasseur...et al."